The Development of Potential Blue Economy Activities in The Marine Protected Area: A Literature Review - Wishanesta, I Kadek Donny; Saskara, Ida Ayu Nyoman; Purbadharmaja, Ida Bagus Putu; Suasih, Ni Nyoman Reni (Technium Sustainability, 2024)
Sustainable tourism is a concept that aims to reduce the negative impacts of tourism on the local environment, society, culture and natural heritage. In this context, research on sustainable tourism and the blue economy is essential to develop a responsible and sustainable tourism industry. The purpose of this study is to analyse the potential development of blue economy activities in marine protected areas, especially in the field of tourism. This research uses a descriptive bibliometric analysis method. Bibliometric analysis shows that the publisher that publishes the most articles about the blue economy in tourism is sustainability blue economy with a total of 200 articles. The use of Network and Density Visualisation software VOSviewer produces a visualisation of themes related to the blue economy, such as "tourism," "social welfare," "political economy," "contribution," "community", and "sustainable blue economy," This research shows the existence of tourism activities on welfare in marine protected areas.